Evidence of Vowel Discrimination Provided by the Acoustic Change Complex. Issue 4 (July 2020) - Cheek, Diane; Cone, Barbara
Abstract : Objectives: The objectives of this study were to measure the effects of level and vowel contrast on the latencies and amplitudes of acoustic change complex (ACC) in the mature auditory system. This was done to establish how the ACC in healthy young adults is affected by these stimulus parameters that could then be used to inform translation of the ACC into a clinical measure for the pediatric population. Another aim was to demonstrate that a normalized amplitude metric, calculated by dividing the ACC amplitude in the vowel contrast condition by the ACC amplitude obtained in a control condition (no vowel change) would demonstrate good sensitivity with respect to perceptual measures of vowel-contrast detection. The premises underlying this research were that: (1) ACC latencies and amplitudes would vary with level, in keeping with principles of an increase in neural synchrony and activity that takes place as a function of increasing stimulus level; (2) ACC latencies and amplitudes would vary with vowel contrast, because cortical auditory evoked potentials are known to be sensitive to the spectro-temporal characteristics of speech. Design: Nineteen adults, 14 of them female, with a mean age of 24.2 years (range 20 to 38 years) participated in this study. All had normal-hearing thresholds. Cortical auditory evoked potentials were obtained from all participants in response to synthesized vowel tokens (/a/, /i/, /o/, /u/), presented in a quasi-steady state fashion at a rate of 2/sec in an oddball stimulus paradigm, with a 25% probability of the deviant stimulus. The ACC was obtained in response to the deviant stimulus. All combinations of vowel tokens were tested at 2 stimulus levels: 40 and 70 dBA. In addition, listeners were tested for their ability to detect the vowel contrasts using behavioral methods. Results: ACC amplitude varied systematically with level, and test condition (control versus contrast) and vowel token, but ACC latency did not. ACC amplitudes were significantly larger when tested at 70 dBA compared with 40 dBA and for contrast trials compared with control trials at both levels. Amplitude ratios (normalized amplitudes) were largest for contrast pairs in which /a/ was the standard token. The amplitude ratio metric at the individual level demonstrated up to 97% sensitivity with respect to perceptual measures of discrimination. Conclusions: The present study establishes the effects of stimulus level and vowel type on the latency and amplitude of the ACC in the young adult auditory system and supports the amplitude ratio as a sensitive metric for cortical acoustic salience of vowel spectral features. Next steps are to evaluate these methods in infants and children with hearing loss with the long-term goal of its translation into a clinical method for estimating speech feature discrimination.